A prospective study of clinical and diagnostic methods of ovarian tumors admitted in a tertiary care hospital and its correlation with histopathology - Madria, Silika; Ghanghoriya, Vineeta; Singh, Kavita N.; Lokwani, Manisha; Tiwari, Ranu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim of the study was to study demographic profile and diagnostic modalities of ovarian tumors and their correlation with histopathological report (HPR). Methods: Prospective observational study conducted in NSCB medical college, Jabalpur from February 2019 to July 2020 on subjects with ultrasonographically diagnosed ovarian tumors. Relevant history obtained, gynecologic examination, investigations recorded. Subjects followed up to collection of HPR and correlation with histopathology done. Results: Out of 120 cases of ovarian tumors, 39.16% were malignant and 60.83% were benign ovarian tumors. Out of 80 premenopausal females, majority (78.75%) had benign ovarian masses. Amongst 40 postmenopausal females, 75% of ovarian masses were malignant. CA125 had sensitivity 76.59%, specificity 76.71% and accuracy 76.66% in diagnosing ovarian malignancy. Amongst 4 RMI scores, RMI 1 has the highest sensitivity and specificity 85.10%, 86.30% respectively. Sensitivity, specificity, and accuracy of ultrasound score was 65.21%, 86.30% and 77.5% respectively. Sensitivity and specificity of clinical diagnosis was 83% and 95.89% respectively and ROC analysis showed clinical diagnosis can accurately predict benign and malignant ovarian tumors in 89% cases. Conclusions: RMI 1 score has the highest sensitivity and specificity in our study. When all 4 methods of diagnosis i.e., RMI Score, ultrasound score, CA125 and clinical diagnosis were compared, clinical diagnosis has highest prediction of malignancy.